178k views
5 votes
D = 3a + 3b
b=d−3a

b=d−3a3

b=3a−d3

b=d−3aa

2 Answers

6 votes


d = 3a + 3b \\ d =3(a + b) \\ (d)/(3) = a + b \\ b = (d)/(3) - a \\ b = (d)/(3) - (a * 3)/(1 * 3) \\ b = (d)/(3) - (3a)/(3) \\ b = (d - 3a)/(3)
The answer is b=d-3a3
User Amorpheuses
by
5.9k points
5 votes

Answer:


b=d-3a3\\b=(d-3a)/(3)

Explanation:

We have the expression
d=3a+3b and we have to solve it for b, this means that we have to clear b.

The first thing we are going to do is subtract 3a from both sides.


d=3a+3b\\\\d-3a=3a+3b-3a\\\\d-3a=3b

Now we have to divide both sides of the equation in 3.


d-3a=3b\\\\(d-3a)/(3)=(3b)/(3) \\\\(d-3a)/(3)=b

Then the correct answer is the second option.


b=d-3a3\\b=(d-3a)/(3)

User Allanvc
by
5.9k points